Indonesia : : the challenge of change edited by Richard W. Baker ... [et al.].. - Baker, Richard W. (St. Martin's Press, 1999)
"A team of Indonesian and American specialists explores the impact of economic growth on twelve major Indonesian institutions, including private and public enterprises, formal political institutions, the armed forces, the bureaucracy, NGOs, the media, and trade unions, amongst others."--BOOK JACKET. "The growing gap between a slow-to-change governing structure and the dynamism of the broader society poses dilemmas - for the next generation of leaders and Indonesia's development. This timely book examines the reactions across society as Indonesia enters a period of major political change."--BOOK JACKET.